Pengaruh Time Management dan Penggunaan Aplikasi Digital terhadap Efektivitas Belajar Mandiri Mahasiswa STIE Widya Praja Tanah Grogot - Muhammad Akbar; Hadijah Hadijah (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to analyze the influence of time management and digital application use on the effectiveness of independent learning among students of STIE Widya Praja Tanah Grogot. The population consisted of all active students, and the sample comprised 146 students who use digital learning applications, selected through purposive sampling. A quantitative method with a survey approach using structured questionnaires was employed. Data were analyzed using multiple linear regression with SPSS version 26. The results indicate that time management has a positive and significant effect on the effectiveness of independent learning (β = 0.385; p < 0.05), digital application use has a positive and significant effect on the effectiveness of independent learning (β = 0.421; p < 0.05), and simultaneously both variables significantly influence the effectiveness of independent learning with a coefficient of determination (R²) of 0.583. These findings imply that strengthening students' time management skills alongside the optimal use of digital learning applications can improve the effectiveness of independent learning.